PERPANJANGAN HAK GUNA BANGUNAN BAGI PERSEROAN TERBATAS DITINJAU DARI PRINSIP KEPASTIAN HUKUM, KEADILAN DAN INVESTASI BERKELANJUTAN MENUJU KESEJAHTERAAN RAKYAT - Puspadma, I Nyoman Alit (Arena Hukum, 2013)
Abstract Land Law is governing the extension of Rights for Building in line with Article 35 paragraph (2), which contains norm fuzziness. The word "may" in standardization in the article raises different interpretations, so it is contrary to the provisions of Article 5 letters f of Law No. 12. Year 2011, which ordered that in every establishment of good laws, one of the conditions that must be met is "clear statement". Rights for Building on the subject referred to in Article 36 paragraph (1) of Land Law, which is a. Citizens of Indonesia and b. legal entities established under Indonesian law and domiciled in Indonesia. Legal entities that are used in this study are a limited liability company. In this regard, there are three problems examined, namely: How is the extension of Rights for Building arranged? How to interpret the provisions of Article 35 paragraph (2) of Land Law if it is associated with principles of legal certainty, justice, and sustainable investment towards social welfare, as well as the legal consequences for Rights For BuildingÂ  for limited liability companyÂ  if the extension is denied? The theories used to analyze the problems are theory classes of Norma (stuffen theory), Legal Certainty theory, theory of justice, and the welfare state theory, while the method of research applied in accordance with normative legal research is the approach of legislation or statute approach, conceptual approach, and the analytical approach, with the source of legal material in the form of the law of primary legal materials, secondary and tertiary. Based on the analysis, the conclusion is as follows: the extension of Rights For BuildingÂ  above state land is stipulated in Article 35 paragraph (2) Land Law in conjunction with Article 26 paragraph (1) Government Regulation 40 of 1996 in conjunction with Article 40 Minister Of Agrarian Regulation/Head National Land Board 9 year 1999, while the extension of Rights For BuildingÂ  over Land Rights ManagementÂ  occurred after the approval of the Land Rights ManagementÂ  holders stipulated in Article 35 paragraph (2) Land LawÂ  Article 26 paragraph (2) Government Regulation 40 of 1996 in conjunction with Article 45 Minister Of Agrarian Regulation/Head National Land Board 9 1999. Rights For Building on the land of private property is set to be not extended, but according to the provisions of Article 29 paragraph (2) Government Regulation 40 of 1996 may be updated. Interpreting the provisions of Article 35 paragraph (2) Land Law should always be associated with Article 2 paragraph (3) and Article 3 of Capital Market Law.Â  In the case of Rights For BuildingÂ  expires, the land is returned to the state when it was coming from State Land or Land Rights ManagementÂ  holder if the land comes from Land Rights Management , and the Limited Liability CompanyÂ  was no longer able to use the land as a place of business or investing. If Limited Liability Company did not get land to run their business (investment), then there will be other legal consequences, namely the dissolution of Limited Liability Company, and employees lay off, which will lead to other consequences, such as economic and social consequence. Key words: extension, rights for building, investment, public welfare Abstrak Hukum Tanah yang mengatur perpanjangan Kuasa untuk Membangun sejalan dengan Pasal 35 ayat (2), yang berisi norma ketidakjelasan. Kata âdapatâ dalam standardisasi dalam artikel menimbulkan interpretasi yang berbeda, sehingga bertentangan dengan ketentuan Pasal 5 huruf f UU No 12. Tahun 2011, yang memerintahkan bahwa dalam setiap pembentukan undang-undang yang baik, salah satu syarat yang harus dipenuhi adalah âpernyataan yang jelasâ. Hak untuk Membangun pada subjek dimaksud dalam Pasal 36 ayat ( 1 ) UU Pertanahan, yang merupakan: a)Warga Indonesia dan b)badan hukum yang didirikan berdasarkan hukum Indonesia dan berkedudukan di Indonesia. Badan hukum yang digunakan dalam penelitian ini adalah perusahaan perseroan terbatas. Dalam hal ini, ada tiga masalah yang diteliti, yaitu: Bagaimana perpanjangan Hak untuk Bangunan diatur ? Bagaimana menafsirkan ketentuan Pasal 35 ayat (2) UU Tanah jika dikaitkan dengan prinsip kepastian hukum, keadilan, dan investasi berkelanjutan menuju kesejahteraan sosial, serta konsekuensi hukum Hak Untuk Bangunan untuk perseroan terbatas jika ekstensi ditolak? Teori yang digunakan untuk menganalisis masalah adalah kelas teori Norma (stuffen theory), teori Kepastian Hukum, teori keadilan, dan teori negara kesejahteraan, sedangkan metode penelitian yang diterapkan sesuai dengan penelitian hukum normatif adalah pendekatan peraturan atau undang-undang pendekatan, pendekatan konseptual, dan pendekatan analitis, dengan sumber bahan hukum dalam bentuk undang-undang bahan hukum primer, sekunder dan tersier. Berdasarkan analisis, kesimpulannya adalah sebagai berikut: perpanjangan Hak Untuk Membangun di atas tanah negara yang diatur dalam Pasal 35 ayat (2) UU Pertanahan juncto Pasal 26 ayat (1) Peraturan Pemerintah 40 Tahun 1996 jo Pasal 40 Menteri of Peraturan Agraria/Kepala Badan Pertanahan Nasional 9 tahun 1999, sedangkan perpanjangan Kuasa Untuk Membangun atas Manajemen Hak atas Tanah terjadi setelah persetujuan pemegang Hak Pengelolaan Lahan diatur dalam Pasal 35 ayat (2) UU Tanah Pasal 26 ayat (2) Peraturan Pemerintah 40 Tahun 1996 jo Pasal 45 Peraturan Menteri of Agraria/Kepala Badan Pertanahan Nasional 9 1999. Hak Untuk Membangun tanah milik pribadi diatur untuk tidak diperpanjang, tetapi menurut ketentuan Pasal 29 ayat (2) Peraturan Pemerintah 40 Tahun 1996 dapat diperbarui`. Menafsirkan ketentuan Pasal 35 ayat (2) UU Pertanahan harus selalu dikaitkan dengan Pasal 2 ayat (3) dan Pasal 3 UU Pasar Modal. Dalam kasus Hak Untuk Membangun berakhir, lahan tersebut dikembalikan ke negara ketika itu datang dari Tanah Negara atau Tanah Hak Pengelolaan pemegang jika tanah berasal dari Manajemen Hak atas Tanah, dan Perseroan Terbatas sudah tidak mampu lagi untuk menggunakan tanah sebagai tempat usaha atau investasi. Jika Perseroan Terbatas tidak mendapatkan lahan untuk menjalankan bisnis mereka (investasi), maka akan ada konsekuensi hukum lainnya , yaitu pembubaran Perseroan Terbatas, dan karyawan PHK, yang akan mengakibatkan konsekuensi lainnya, seperti konsekuensi ekonomi dan sosial. Kata kunci: ekstensi, hak untuk membangun, investasi, kesejahteraan masyarakat